Why Do Women Earn Less than Men? Evidence from Bus and Train Operators - Bolotnyy, Valentin; Emanuel, Natalia (Journal of Labor Economics, 2022)
Female workers earn $0.89 for each male-worker dollar even in a unionized workplace, where tasks, wages, and promotion schedules are identical for men and women by design. Using administrative time-card data on bus and train operators, we show that this earnings gap can be explained by female operators taking fewer hours of overtime and more hours of unpaid time off than male operators. Female operators, especially those with dependents, pursue schedule conventionality, predictability, and controllability more than male operators. While reducing schedule controllability can limit the earnings gap, it can also hurt female workers and their productivity.